2016
DOI: 10.1016/j.heliyon.2016.e00135
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric parameters of normal full term placenta of Sudanese women

Abstract: The aim of the study was to provide values for morphometric parameters of histological components of normally delivered full term placentas of Sudanese women and compare them with reported parameters for other ethnic groups. A total of 200 histological sections, stained with hematoxylin and eosin and trichrome stains were used to give a final sample of 1000 fields saved as PowerPoint images for histomorphometry. A systematic random sampling procedure was adopted to ensure the optimum sample size that keeps the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…The presence of fetal and maternal blood supply to the placenta adds to the complexity of interpreting the obtained perfusion images. Overall, we expect a larger contribution to the signal from maternal than fetal blood (at GA ~30 weeks relative volumes are roughly 70% vs 30% 38 ), assuming equivalent labeling efficiency on maternal and fetal sides.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of fetal and maternal blood supply to the placenta adds to the complexity of interpreting the obtained perfusion images. Overall, we expect a larger contribution to the signal from maternal than fetal blood (at GA ~30 weeks relative volumes are roughly 70% vs 30% 38 ), assuming equivalent labeling efficiency on maternal and fetal sides.…”
Section: Discussionmentioning
confidence: 90%
“…Assuming that DEPs are round spheres with a mean diameter of 330 nm (according to the manufacturer’s Information, d(0.9), https://www-s.nist.gov/srmors/certificates/1650b.pdf ), a particle has a volume of 1.88 × 10 –20 m 3 and a mass of 3.38 × 10 –14 g with a density of 1.80 × 10 6 g/m 3 [ 31 ]. The average volume of a placenta is 500 cm 3 [ 32 ], leading to an estimated deposition of 353 μg of particles per placenta or 17.7 μg particles per cotyledon (20 cotyledons per placenta) during pregnancy. Taking into account the potential loss of particles to the perfusion system, some diffusion of the suspension into the surrounding tissues, and incomplete tissue uptake of the applied particles, a 3× safety margin was included in the calculation resulting in an applied concentration of 0.45 μg/mL (3 × 17.7 µg/120 mL PM) in the maternal circulation for the perfusion studies.…”
Section: Resultsmentioning
confidence: 99%
“…There was not significant difference with in low birth placenta (159). Heidary 11 et al reported percentage volumes of the villi (66%) and inter villous space (34%) in cases of placenta previa of Iranian women whereas Abdalla 12 et al (2016) found out values for the normally implanted placenta in Sudanese women as 65%. Thus, it indicates that the site of implantation within the endometrium has no impact on the volume densities of the placental villi and the inter villous space.…”
Section: Discussionmentioning
confidence: 99%